THE MOST RELEVANT ATTRIBUTES ON PURCHASE DECISION OF BEEF: A BEST-WORST SCORE APPROACH/Os atributos mais relevantes na decisão de compra de carne bovina: uma aproximação pela Pontuação Melhor-Pior - Groot, Etiénne (Informe GEPEC, 2020)
The aim of this study was to evaluate the most important attributes on beef purchase decision in the city of Dracena, State of Sao Paulo, Brazil. It was carried out face-to-face interviews using a structured questionnaire, in which was performed a Best-Worst Discrete Choice Experiment of case 1. The answers were analysed by Best-Worst Score. The preference heterogeneity was assessed through factorial analysis. It was found that the appearance of beef is the most important attribute on consumers’ purchase decision and it is followed by its freshness, packaging/expiry date, smell and texture. It was observed the existence of groups of consumers with different preferences by factors that group the evaluated attributes. For example, men attach more importance to the attributes (organic and fat amount) of the healthy dimension while women give more importance to the attributes from expiry data/packaging dimension.